Precision analysis of mutant U2AF1 activity reveals deployment of stress granules in myeloid malignancies - Biancon, Giulia; Joshi, Poorval; Zimmer, Joshua T.; Hunck, Torben; Gao, Yimeng; Lessard, Mark D.; Courchaine, Edward; Barentine, Andrew E.S.; Machyna, Martin; Botti, Valentina; Qin, Ashley; Gbyli, Rana; et al. (Molecular cell, 2022)
Splicing factor mutations are common among cancers, recently emerging as drivers of myeloid malignancies. U2AF1 carries hotspot mutations in its RNA-binding motifs; however, how they affect splicing and promote cancer remain unclear. The U2AF1/U2AF2 heterodimer is critical for 3′ splice site (3′SS) definition. To specifically unmask changes in U2AF1 function in vivo, we developed a crosslinking and immunoprecipitation procedure that detects contacts between U2AF1 and the 3′SS AG at single-nucleotide resolution. Our data reveal that the U2AF1 S34F and Q157R mutants establish new 3′SS contacts at −3 and +1 nucleotides, respectively. These effects compromise U2AF2-RNA interactions, resulting predominantly in intron retention and exon exclusion. Integrating RNA binding, splicing, and turnover data, we predicted that U2AF1 mutations directly affect stress granule components, which was corroborated by single-cell RNA-seq. Remarkably, U2AF1-mutant cell lines and patient-derived MDS/AML blasts displayed a heightened stress granule response, pointing to a novel role for biomolecular condensates in adaptive oncogenic strategies. [Display omitted] •freCLIP-seq dissects in vivo U2AF1 RNA binding at single-nucleotide resolution•U2AF1 mutations create de novo 3′ splice site contacts that alter RNA splicing•Binding and splicing integration uncovers alterations in stress granule components•U2AF1-mutant MDS/AML cells exhibit enhanced stress granule response Biancon et al. unmask a stress granule signature in U2AF1 mutant myeloid malignancies via multiomics dissection of RNA binding, splicing, and turnover. They document novel mutant-specific U2AF1-RNA binding peaks at 3′ splice site positions, determining aberrant splice outcomes. U2AF1 mutant cells display enhanced stress granule formation and stress resistance.